Cost Elements of Offshore Platform Decommissioning in Malaysia - Rosli, Nur Heiyqal Hidayat (Universiti Teknologi PETRONAS, 2017)
The purpose of this study is to identify the cost elements of offshore platform decommissioning in Malaysia. Decommissioning, specifically in Malaysia is still in its infancy and immature phase compared to others region such as Gulf of Mexico and North Sea where the operators there are experienced enough in conducting decommissioning. Due to the lack of experience of decommissioning in Malaysia, the operators are lacking of knowledge to conduct decommissioning especially in determining the way to have a low cost decommissioning process. Moreover, there is no study or literature about the cost elements has been published in Malaysia, even in Southeast Asia as well. Therefore, this study basically identifies the cost elements of decommissioning in Malaysia from set of interviews with representative from different companies which have involved in any decommissioning projects. Then, the identified cost elements are prioritized based on their impact towards the total cost of decommissioning in order to identify the significant cost elements. It is followed by analysing the significant cost elements which focus on justification of why the elements are significant. At the end, few solutions are proposed in order to minimize the impact of the significant cost elements towards the total cost of decommissioning.